WHEN RELIGIOUS LANGUAGE IS RIGHT: A Case for God’s Anthropomorphic Identities - Peter Ogenefavwe Ottuh (MAHABBAH: Journal of Religion and Education, 2022)
Is it possible to think about God without anthropomorphizing him? The fact that God has both anthropomorphic and non-anthropomorphic characteristics adds to theological confusion. Individual variances in God's views might be a reflection of how individuals understand God's portrayals. Intellectuals have argued for ages that theistic conceptions of God are excessively anthropomorphic, perplexing, and complex. The paper focused on religious language and God’s anthropomorphic identities. It employed a historico-comparative approach using library resources. The finding provides light on the limitations and potential of philosophico-religious transmission of the complex idea of anthropomorphism and offers a critical, constructive, and interpretive avenue for intellectual dialogue.